In the Debt Crisis Axis Income-based Determinants of Insurance Premium Production In Europe - TUNAY, KAŞİF BATU; TUNAY, NECLA (EGE UNIV, FAC ECONOMICS & ADMIN SCIENCES, 2018)
In this study, it is analyzed the income based determinants of premiums that produced by insurance companies in developed and emerging economies from the European case. Within the framework of the debt crisis in Europe, it has also been investigated how premium production of insurance companies is affected by crises in countries where wealth and insurance awareness are high. The analyzes were performed using system dynamic panel data models and data from 32 countries. Findings indicate that premium production of insurance companies is affected by income-based determinants such as per capita purchasing power and per capita savings. The variables such as output gap and unemployment that indicating volume of the economic activity have also an impact on the insurance premiums. In addition, it was determined that the serious crises that took place behind one after another also reduced premium production.
Keywords: Insurance; premium production; financial crisis; system dynamic panel data; UNIT-ROOT TESTS; PANEL-DATA; ERROR-COMPONENTS; MODELS